2007
DOI: 10.1167/iovs.07-0251
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IL-17+Interphotoreceptor Retinoid-Binding Protein-Specific T Cells in Experimental Autoimmune Uveitis

Abstract: IL-17(+) T cells can be readily detected among activated autoreactive and bystander T cells and may play a major role in the pathogenesis of EAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 47 publications
10
128
1
1
Order By: Relevance
“…[12][13][14] In the previous study, we reported that both IL-17 + and IFN-γ + IRBP-specific T cells are uveitogenic. 15) Meanwhile, we found that in QKL group and Dex group, the differentiation of IFN-γ-expressing CD4 + T cells and IL-17-expressing CD4 + T cells are lower than control cells. We also observed that the relative expression of Th1-and Th17-cytokines at the mRNA level were markedly reduced after treatment with Qingkailing injection and Dexamethasone.…”
Section: Discussionmentioning
confidence: 84%
“…[12][13][14] In the previous study, we reported that both IL-17 + and IFN-γ + IRBP-specific T cells are uveitogenic. 15) Meanwhile, we found that in QKL group and Dex group, the differentiation of IFN-γ-expressing CD4 + T cells and IL-17-expressing CD4 + T cells are lower than control cells. We also observed that the relative expression of Th1-and Th17-cytokines at the mRNA level were markedly reduced after treatment with Qingkailing injection and Dexamethasone.…”
Section: Discussionmentioning
confidence: 84%
“…In the model of experimental autoimmune encephalomyelitis, the antigen specific Th17 cells were reported (21), and in the model of experimental autoimmune uveitis, both the antigen-specific and non-antigen specific Th17 cells were present (22). To explore whether the production of IL-17 by γδ T cells is antigen specific or not, we expanded peripheral blood γδ T cells from PBMCs cultured with M. tb-HAg that predominantly stimulate human γδ T cells in vitro, and found the expanded γδ T cells differentiated into effective cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in patients, CD8 + T cells producing IL-17 can be identified in chronic inflammatory lesions such as psoriatic lesions (32) and multiple sclerosis plaques (30). Animal models corroborate the implication of IL-17-producing CD8 + T cells in a wide variety of immune conditions (22,(33)(34)(35)(36). Adoptive transfer experiments of Tc17 cells have suggested that their ability to clear influenza virus and to protect against tumor are related to the plasticity of the Tc17 lineage (22,37).…”
mentioning
confidence: 86%